Management of Centrality Education and Training Students Sports (PPLOP) Pencaksilat - Yogaswara, Andre; Sugiyanto, Sugiyanto; Purnama, Sapta Kunta; Sugiharto, Sugiharto; Septianingrum, Kartika (Journal of Education, Health and Sport, 2018)
This research aims to find out the implementation of the organization, management of human resources, sports facilities, finance, development of PPLOP pencaksilat in Central Java. The research method used Enterpretive Study techniques. This study explains, interprets, identifies, and describes the implementation of management pencaksilat the centrality education and exercises students sports (PPLOP) Central Java. Techniques for collecting data through observation, interviews, and documents. The results are 1. The implementation of PPLOP organizational management has been going well. It can be seen from the existence of a complete management arrangement, and clear objectives. 2. The implementation of human resource management has gone well. This can be seen from the fulfillment of the quota of athletes and coaches. 3. Implementation The management of sports facilities is quite good even though the existing facilities are still lacking but the utilization of facilities is carried out optimally. 4. The implementation of financial management has been going well, even though there are still financial constraints but still can be overcome by the manager. 5. The implementation of management of achievement guidance has been going well. Academic coaching athletes are fostered through public schools or homeschooling. Religious development is carried out in schools and in the hall.